ANALISIS KEBUTUHAN SISWA TERHADAP MODUL BAHASA INDONESIA:SEHATLAH RAGAKU BERBASIS KEARIFAN LOKAL JEPARA - Suci Rahayu; Erik Aditia Ismaya; Lintang Kironoratri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2023)
The quality of human resources in education can be improved by improving and developing learning processes and tools. One of them is developing modules in the learning process. The purpose of this study was to analyze students' needs for the development of an Indonesian language module on healthy body material in grade IV SD by integrating Jepara culture. The method used in this research is to use qualitative research methods with descriptive research types. The subjects of this study were a class IV teacher and 14 fourth grade students at SD Negeri 1 Tritis. Data collection instruments were carried out using observation, interview and documentation techniques. The result of this research is that it is necessary to produce modules based on local wisdom in accordance with the environment around students to facilitate students' understanding of material and readings in learning Indonesian and this is expected to improve student achievement for the better.